Analysis of Heavy Equipment Productivity Tower Crane in The Construction Project of Sultan Maulana Hasanudin State Islamic University Building - Maddeppungeng, Andi; Asyiah, Siti; Intari, Dwi Esti; Hakim, Bahtiar Imanul; Setiawati, Dwi Novi (Jurnal Fondasi, 2023)
Building construction in Indonesia has increased rapidly; according to the BPS (Badan Central Statistics), in 2020, building construction from 2016–2019 will have 189 buildings in Jakarta. The construction includes apartments, hotels, offices, and campuses. While productivity measurements are useful as information for the company to evaluate the trends of its productivity developments over time, information from these results will later be used for reference in correcting previous shortcomings. This research aims to determine how long a tower crane’s cycle time, productivity, and operating costs are. This research was carried out on the construction project of the State Islamic University of Sultan Maulana Hasanuddin Banten. The study was conducted by observing the tower crane for six days. From data collection, whether cycle time, productivity, or operating cost, the data analysis used in this study is an analysis using productiveness formulas, cycle times, and operating costs. From the analysis of the data, it can be known that the cycle time of the tower crane heavy tool on April 25, 2022, to April 29, 2022, gained an average of 0.311 hours for the average productivity of the tower crane on April 25, 2022, until April 29, 2022, which is 9662.131 kg/hour, while the operating cost of the crane tower was Rp. 575.037.37 per hour